International Strategy of Junior Achievement - Müller, Josef (2011)
Junior Achievement is an international non-profit educational organization. It operates in more than 120 countries around the world and serves more than 10 million students every year. The aim of this paper is to analyze the international strategy of Junior Achievement and to draw out recommendations for its future operations and for operations of similar entities. The paper presents an inimitable view on the organization from the author, leader of one the national organizations within the Junior Achievement network. The paper provides a detailed view into the history of the organization. It also describes the development and current state of selected national organization in United Kingdom, Estonia and Czech Republic. The last chapter analyzes strategies of Junior Achievement at worldwide, regional and national levels. The chapter also compares and contrasts the strategies in order to find similarities and differences and to draw out basic recommendations for different levels of Junior Achievement operations based on the comparison and the author's personal experience.